Pharmacological clearance of senescent cells improves survival and recovery in aged mice following acute myocardial infarction. Issue 3 (28th March 2019) - Walaszczyk, Anna; Dookun, Emily; Redgrave, Rachael; Tual‐Chalot, Simon; Victorelli, Stella; Spyridopoulos, Ioakim; Owens, Andrew; Arthur, Helen M.; Passos, João F.; Richardson, Gavin D.
Abstract: Cardiovascular disease is the leading cause of death in individuals over 60 years old. Aging is associated with an increased prevalence of coronary artery disease and a poorer prognosis following acute myocardial infarction (MI). With age, senescent cells accumulate in tissues, including the heart, and contribute to age‐related pathologies. However, the role of senescence in recovery following MI has not been investigated. In this study, we demonstrate that treatment of aged mice with the senolytic drug, navitoclax, eliminates senescent cardiomyocytes and attenuates profibrotic protein expression in aged mice. Importantly, clearance of senescent cells improved myocardial remodelling and diastolic function as well as overall survival following MI. These data provide proof‐of‐concept evidence that senescent cells are major contributors to impaired function and increased mortality following MI and that senolytics are a potential new therapeutic avenue for MI. Abstract : Aging and the accumulation of senescence promote adverse cardiac remodelling and fibrosis. In the event of a myocardial infarction (MI), aged mice demonstrate reduced cardiac function and high mortality. Treatment of aged mice with the senolytic navitoclax alleviated adverse myocardial remodelling, improved the maintenance of cardiac function and increased survival following MI.